ALTERNATIF PENYELESAIAN KONFLIK WARIS MELALUI MEDIASI DALAM MASYARAKAT DAYAK BERAGAMA ISLAM DI DESA MENUKUNG, MELAWI - Hardiyanti, Siti (Faculty of Law, Universitas Tanjungpura, 2025)
Abstract The settlement of disputes over the distribution of inheritance property in the Muslim Dayak community in Menukung Village, Melawi Regency often results in conflicts between heirs. The division of inheritance in Menukung Village is still by way of equal distribution or by family or also by way of division of inheritance according to local customary law. Therefore, usually from the distribution of the inheritance there are still heirs who do not agree with the results of the distribution and demand that the distribution of their inheritance be distributed in accordance with Islamic law. This research aims to examine information about the factors that cause inheritance disputes, the distribution of inheritance through mediation and the efforts of disputing heirs through mediation in the distribution of inheritance. The formulation of the problem proposed in this study, namely